Inventing a socialist nation : Heimat and the politics of everyday life in the GDR, 1945 - 1990 - Palmowski, Jan 1965- (New studies in European history, 2009)
"This study explores the significance and the meanings of nation, homeland and patriotism under the conditions of socialism in the German Democratic Republic (GDR). The GDR hardly constitutes a 'typical' socialist state. A central pillar to the Soviet domination of Eastern Europe and a frontline state in the Cold War, the GDR remained tightly under Soviet control until 1989. What made the GDR unique within the socialist bloc was the absence of a distinctive nationhood, which was constantly challenged by the larger and more prosperous part of Germany, the Federal Republic of Germany (FRG). For this reason, those scholars who have considered the issue have argued that in the GDR, nationalism played next to no role 'as movement, as political idea, and as popular sentiment' before 1989. The idea of the nation, such as it existed, was closely tied to the promise of consumerism in the FRG - 'DM Nationalismus', as Jurgen Habermas called it. National identity appeared to be of little consequence in assessing the history of the GDR and its collapse. Even German reunification 'was not so much a nationalist idea as a route for East Germans to an imagined world of prosperity and freedom'"--Provided by publisher